Rozrywkowe oblicze radia komercyjnego - Czarnek Wnuk, Paulina (Wydawnictwo Uniwersytetu Łódzkiego, 2026)
The book The entertainment side of commercial radio presents in a comprehensive way the strategies of selected private radio stations, i.e. Radio Eska, RMF FM and Radio Zet, related to the provision of entertainment by them. The aim of this publication was to analyze the offer of commercial radio stations in terms of entertainment content and activities present in them. The research hypothesis, which was verified in the course of the considerations, indicated that they (these contents and actions) constitute the core of the transmission of formatted private radio stations. The chosen research method was the analysis and logical construction with the elements of content analysis and case study, supported by theoretical considerations based on the literature on the subject. In the theoretical part, the author reviews various research positions in relation to entertainment and phenomena close to it (game, fun, free time, carnival), looks at the ludic role of the media from the perspective of, inter alia, functionalism or the critical theory, and finally characterizes the commercial radio sector. In the analytical chapters, she presents aerial and non-aerial entertainment activities, as well as initiatives taken in the space of the so-called new media (they are preceded by a short historical outline relating to the presence of play in the audio medium). The conclusions from the observation and interpretation of the discussed actions confirm the hypothesis articulated at the beginning. The entertainment offer of commercial broadcasters is quite extensive, though not always valuable, and is a combination of what they offer to the audience on the air, in the non-programming space or on the Internet.